Regulation of the physiology and virulence of Ralstonia solanacearum by the second messenger 2',3'-cyclic guanosine monophosphate - Li, Xia (2024)
Previous studies have demonstrated that bis-(3',5')-cyclic diguanosine monophosphate (bis-3',5'-c-di-GMP) is a ubiquitous second messenger employed by bacteria. Here, we report that 2',3'-cyclic guanosine monophosphate (2',3'-cGMP) controls the important biological functions, quorum sensing (QS) signaling systems and virulence in Ralstonia solanacearum through the transcriptional regulator RSp0980. This signal specifically binds to RSp0980 with high affinity and thus abolishes the interaction between RSp0980 and the promoters of target genes. In-frame deletion of RSp0334, which contains an evolved GGDEF domain with a LLARLGGDQF motif required to catalyze 2',3'-cGMP to (2',5')(3',5')-cyclic diguanosine monophosphate (2',3'-c-di-GMP), altered the abovementioned important phenotypes through increasing the intracellular 2',3'-cGMP levels. Furthermore, we found that 2',3'-cGMP, its receptor and the evolved GGDEF domain with a LLARLGGDEF motif also exist in the human pathogen Salmonella typhimurium. Together, our work provides insights into the unusual function of the GGDEF domain of RSp0334 and the special regulatory mechanism of 2',3'-cGMP signal in bacteria.